Systematic review and meta-analysis: screening tools for attention-deficit/hyperactivity disorder in children and adolescents - Mulraney, Melissa; Arrondo, Gonzalo; Musullulu, Hande; Iturmendi-Sabater, Iciar; Cortese, Samuele; Westwood, Samuel J.; Donno, Federica; Banaschewski, Tobias; Simonoff, Emily; Zuddas, Alessandro; Döpfner, Manfred; Hinshaw, Stephen P.; et al. (Journal of the American Academy of Child and Adolescent Psychiatry, 2022)
Objective - This systematic review and meta-analysis aimed to determine the accuracies of a broad range of screening tools for attention-deficit/hyperactivity disorder (ADHD) in children and adolescents, and to compare the diagnostic accuracy of tools between population-based and clinical/high-risk samples, and across reporters. - Method - MEDLINE, PsycINFO, EMBASE, and PubMed were searched up until February 20, 2020, with no language restrictions. Studies reporting diagnostic accuracy of a screening tool against a diagnosis of ADHD in children and adolescents <18 years of age were eligible for inclusion. Meta-analyses were undertaken to provide pooled estimates of the area under the curve (AUC), and sensitivity and specificity of groups of measures. - Results - A total of 75 studies published between 1985 and 2021 reporting on 41 screening tools that were grouped into 4 categories (Achenbach System of Empirically Based Assessment [ASEBA], DSM-IV symptom scales, SDQ, and Other Scales) were retained. The pooled AUC for studies using a combined ADHD symptoms score was 0.82 (95% CI = 0.78−0.86), although this varied considerably across reporters (0.67-0.92) and populations (CI = 0.60−0.95). None of the measures met minimal standards for acceptable sensitivity (0.8) and specificity (0.8). - Conclusion - Most tools have excellent overall diagnostic accuracy as indicated by the AUC. However, a single measure completed by a single reporter is unlikely to have sufficient sensitivity and specificity for clinical use or population screening.
Gesehen am 16.11.2022